MENGANALISIS POTENSI SUMBER DAYA ALAM DI DESA LAKWATI, KECAMATAN ALOR TENGAH UTARA - Heronike Mangmani; Loni Sarlota Mau Klaping; Jero Sion E. Blegur; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This research aims to analyze the potential of natural resources found in Lakwati Village, Alor Tengah Utara District, Alor Regency. The research method uses a qualitative descriptive approach through field observations, interviews with the village head, and the local community as well as documentation. The results of this research show that Lakwati village has several superior commodities, such as lime, candlenut, Japanese pumpkin and cloves which have the potential to be developed as a source of community income. Apart from that, fertile land conditions and a supportive climate are supporting factors for the development of the plantation sector. This research concludes that the utilization of natural resource potential in Lakwati Village has a great opportunity to improve community welfare if managed sustainably and supported by the Village development program.